On Constructivism: social construction of reality and research practice - Pérez Rubio, Ana María (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2012)
The social sciences in its classical version – adopting as model the natural sciences – concentrated in the study of empirical facts with the pretension to arrive at an objective knowledge of reality. From this approach the social sciences became a theoretical representation of nature, while the facts constituted themselves with independence of human mind. But during the last century the basis of knowledge – the ontological and epistemological status as much of the object as subject – were put into question. In this new approach, the language – and the communication – comes to be the resources through which individuals and groups construct their daily life and the main interest is to reveal the process of construction of sense. This perspective radically modifies the prevailing paradigm in social sciences. However, the discussion about its validity has not been solved, in particular because it involves some of the main questions of modernity and posmodernity. Thus, the article sets out to consider the main elements that form this approach, identifying the different currents that coexist in its inland, the main critics and specifically the consequences that derive so much from the point of view of the production of knowledge as in relation to the study of society